Զրադաշտականությունը և հայերին հավատափոխելու նրա փորձերը (IV-V դդ.) - Արմեն Տեր-Գրիգորյան (ՀՀ ԳԱԱ հրատ.)
Зороастризм является древнейшей религией, которая получила широкое распространение во времена Сасанидов. С 301 года начинаются ожесточенные бои армянского народа с Сасанидами за защиту своей собственной религии, потому что почти все сасанидские цари требовали от армян отказаться от христианства и в качестве государственной религии принять зороастризм. Zoroastrianism is one of the world’s oldest monotheistic religions, which widely spread during the Sassanid dynasty. The Armenians’ struggles against the Sassanids to preserve Christianity since 301, in view of the fact that almost all Sassanid kings used to force the Armenians to renounce Christianity and convert to Zoroastrianism and accept it as the state religion.
Keywords: Christianity; History of the Armenian Church; Ancient History